2019
DOI: 10.1155/2019/3035125
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Curcumol Inhibit NF-κB and TGF-β1/Smads Signaling Pathways in CSE-Treated RAW246.7 Cells

Abstract: E-Zhu (Curcuma zedoaria) is known as a classical traditional Chinese medicine and widely used in the treatment of cancers, cardiovascular disease, inflammation, and other diseases. Its main components include curcumol and curcumin, which have anti-inflammatory and antifibrosis effects. Here we established an in vitro inflammatory injury model by stimulating RAW246.7 cells with cigarette smoke extract (CSE) and detected the intervention effects of curcumin and curcumol on CSE-treated Raw246.7 macrophage cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“… 42 There is a low basal COX2 expression in neurons of the healthy brain; however, pathological conditions, such as astrocyte activation, strongly induce COX2 in the brain. 43 The prevention of astrocyte activation and inhibition of HMGB1, RAGE and TLR4, as shown in our study, together with NF‐κB inhibition by curcuma , reported previously, 40 , 44 point to the fact that its anti‐inflammatory effects may play an important role in the development of AD. In clinical trials, curcumin appears to have no major side effects in patients with AD.…”
Section: Discussionsupporting
confidence: 79%
“… 42 There is a low basal COX2 expression in neurons of the healthy brain; however, pathological conditions, such as astrocyte activation, strongly induce COX2 in the brain. 43 The prevention of astrocyte activation and inhibition of HMGB1, RAGE and TLR4, as shown in our study, together with NF‐κB inhibition by curcuma , reported previously, 40 , 44 point to the fact that its anti‐inflammatory effects may play an important role in the development of AD. In clinical trials, curcumin appears to have no major side effects in patients with AD.…”
Section: Discussionsupporting
confidence: 79%
“…NF-κB is one of the targets for Curcumin. Curcumin inhibits the NF-κB signaling pathway, and reduces the release of proinflammatory factors in RAW246.7 cells treated by cigarette smoke extracts [20]. Inhibition of NF-κB may be the main mechanism for the anti-inflammatory effect of Curcumin [21].…”
Section: Discussionmentioning
confidence: 98%
“…Structurally, however, curcumol and curcumin differ, which suggests that they might possess different bioactivity (19). For example, the inhibitory effect of curcumol on the production of inflammatory factors in RAW246.7 cells was more significant than that of curcumin (20). Currently, the effects of the combination of curcumol and metformin on the progression of TNBC are unclear.…”
Section: Introductionmentioning
confidence: 99%